Rojas Zorrilla’s Queens: new ways to understand exercise of power (Castilla. Estudios de Literatura, 2023)
Rojas Zorrilla, one of the most important playwrights of the Calderonian generation –and one of the Queen’s favorites, added himself to the analysis of exercise of monarchical power, combining some works which depicted ideal leaders with others, the big majority, in which he criticized improper behaviors by certain kings –all the previous with a definite didactic aim. From this corpus, we will analyze three titles which outstand the rest due to their originality and subversive character: Los áspides de Cleopatra; Santa Isabel, reina de Portugal; and El mejor amigo, el muerto (collaborative). Their protagonists are women who understand her work in a different way, in a more popular conception that somewhat separates them from the male referents from 16th and 17th Centuries. We will study how they reign, how their rebellious ideas might get the audience, and what was the final objective of the Toledan author.
Keywords: Rojas Zorrilla; queens; exercise of power; monarchy; propaganda